2021
DOI: 10.3390/plants10122717
|View full text |Cite
|
Sign up to set email alerts
|

Tragia L. Genus: Ethnopharmacological Use, Phytochemical Composition and Biological Activity

Abstract: Tragia L. is a genus of plants belonging to the Euphorbiaceae family with worldwide intertropical distribution, composed of more than 150 species. In this literature review, 26 species of the genus used as medicinal plants were found, mainly in East Africa and the Indian subcontinent, with a variety of uses among which antibacterial, anti-inflammatory, anticancer and reproductive health are most common. Research has been done on a few of the species, mostly those of the Old World, with emphasis on four of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Although there chemical composition ofT. hispida , is not known it has been shown that related species such as T. involucrata is rich in flavonoids, particularly in several glycosides and derivatives of quercetin 15,21 . Flavonoids have shown to inhibit sPLA2 activity, and has shown to inhibit sPLA2 in synovial fluid but not from pancreatic fluid, showing that T.hispidia is most likely to have compounds that inhibit sPLA2 II group of enzymes 22 .…”
Section: Characterization Secondary Metabolites Of Butanol Fraction O...mentioning
confidence: 99%
“…Although there chemical composition ofT. hispida , is not known it has been shown that related species such as T. involucrata is rich in flavonoids, particularly in several glycosides and derivatives of quercetin 15,21 . Flavonoids have shown to inhibit sPLA2 activity, and has shown to inhibit sPLA2 in synovial fluid but not from pancreatic fluid, showing that T.hispidia is most likely to have compounds that inhibit sPLA2 II group of enzymes 22 .…”
Section: Characterization Secondary Metabolites Of Butanol Fraction O...mentioning
confidence: 99%
“…Arg. Brazil NS [18] Tragia volubilis L. Mexico to Argentina See below [10] Tragia yucatanensis Millsp. Mexico, Belize, Honduras Burns, rheumatism [19] In addition to medical uses, there are other reported activities of the New World species: T. biflora is allelopathic against water plants; pounded, boiled T. brevispica taken orally is reportedly aphrodisiac in Uganda [20]; and T. gracilis is used in Cuba for Santería religious uses [21].…”
Section: The Genus Tragia (Euphorbiaceae)mentioning
confidence: 99%
“…Research on the genus centers on antidiabetic and anti-inflammatory activity. Additionally, investigations have revealed significant biological activity and low toxicity in relation to its antimalarial, antibacterial, antitumor, and diuretic effects [10]. More than sixty New World Tragia species comprise almost 40% of the total species in the genus.…”
Section: The Genus Tragia (Euphorbiaceae)mentioning
confidence: 99%
“…Although there chemical composition of T. hispida, is not known it has been shown that related species such as T. involucrata is rich in flavonoids, particularly in several glycosides and derivatives of quercetin [15,21]. Flavonoids have shown to inhibit sPLA2 activity, and has shown to inhibit sPLA2 in synovial fluid but not from pancreatic fluid, showing that T.hispidia is most likely to have compounds that inhibit sPLA2 II group of enzymes [22].…”
Section: Characterization Secondary Metabolites Of Butanol Fraction O...mentioning
confidence: 99%